2022
DOI: 10.3389/fgene.2022.939175
|View full text |Cite|
|
Sign up to set email alerts
|

Relevance of RNA N6-Methyladenosine Regulators for Pulmonary Fibrosis: Implications for Chronic Hypersensitivity Pneumonitis and Idiopathic Pulmonary Fibrosis

Abstract: N6-methyladenosine (m6A) modification plays a pivotal role in post-transcriptionally regulating gene expression and biological functions. Nonetheless, the roles of m6A modification in the regulation of chronic hypersensitivity pneumonitis (CHP) and idiopathic pulmonary fibrosis (IPF) remain unclear. Twenty-two significant m6A regulators were selected from differential gene analysis between the control and treatment groups from the GSE150910 dataset. Five candidate m6A regulators (insulin-like growth factor bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In our previous study, we demonstrated that two distinct m6A patterns were associated with fibrosis and might distinguish CHP and IPF 38 . Inspired by these findings, we analyzed expression patterns of the major m5C regulators altered in GSE150910 and found that they played a key role in occurrence and development of CHP and IPF.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous study, we demonstrated that two distinct m6A patterns were associated with fibrosis and might distinguish CHP and IPF 38 . Inspired by these findings, we analyzed expression patterns of the major m5C regulators altered in GSE150910 and found that they played a key role in occurrence and development of CHP and IPF.…”
Section: Discussionmentioning
confidence: 92%
“…Significant overexpression of m 6 A regulators IGFBP3, IGFBP5, and ALKBH6 characterizes IPF patients, with a positive association between elevated METTL16 levels and ALKBH6, highlighting the pivotal role of m 6 A modification regulators as IPF biomarkers. 173 The analysis of sequencing data from IPF patients in the GEO database highlights METTL3, a regulatory factor involved in m 6 A methylation, as a promising candidate for predicting risk or assessing prognosis in IPF. 174 METTL3-mediated cir-cRNA m 6 A modifications have been confirmed to correlate with SiO 2 -induced lung fibroblast activation and migration, as well as pulmonary fibrosis outcomes.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%